2008
DOI: 10.1002/jctb.2081
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the solvent extraction of rare earths from nitrate media with a combination of di‐(2‐ethylhexyl)phosphoric acid and sec‐octylphenoxyacetic acid

Abstract: BACKGROUND: Di-(2-ethylhexyl)phosphoric acid (D2EHPA, H 2 A 2 ) has been used extensively in hydrometallurgy for the extraction of rare earths, but it has some limitations. Synergistic extraction has attracted much attention because of its enhanced extractabilities and selectivities. In the present study, sec-octylphenoxyacetic acid (CA12, H 2 B 2 ) was added into D2EHPA systems for the extraction and separation of rare earths. The extraction mechanism of lanthanum with the mixtures and the separation of lanth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 11 publications
(13 reference statements)
0
17
0
Order By: Relevance
“…CA12 is considered an effective carboxylic acid extractant for REs extraction and has been studied extensively in recent years, so we compare HA with CA12 in Fig. .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…CA12 is considered an effective carboxylic acid extractant for REs extraction and has been studied extensively in recent years, so we compare HA with CA12 in Fig. .…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that the extraction pH value for REs with sec‐nonylphenoxyacetic acid (CA100) can be lowered to 2.5 in heptane . In addition, several types of synergistic systems, such as 2‐ethylhexylphosphonic acid mono‐(2‐ethylhexyl) ester/CA100, bis(2,4,4‐trimethylpentyl)phosphinic acid/CA100 and di‐(2‐ethylhexyl)phosphoric acid/ sec‐octylphenoxyacetic acid (CA12), have also been used to improve the extraction ability and selectivity of phenoxyacetic acid …”
Section: Introductionmentioning
confidence: 99%
“…The case of excess amine nitrate in the organic phase compared with the stoichiometry of an inorganic salt extraction and salting-out the metal (excluding solvation process and at x e x s D high extractant excess) can be described by Eqs. (7) and (8) as follows:…”
Section: Resultsmentioning
confidence: 99%
“…This process is usually carried out using countercurrent extraction cascades containing several dozen successive extractors. Organophosphorus extractants, such as TBP, di-(2ethylhexyl) phosphoric acid (D2EHPA), dialkylphosphinic, dialkyldithio phosphinic and carboxylic acids are mainly used to produce REM [3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…A variety of extractants have been used in synergistic extraction including: acidic organophosphorus extractants,3–11 neutral organophosphorus extractants,4, 5, 12–14 carboxylic acids,6, 8–12 amines,15 β‐diketones,13, 14, 16–27 crown ethers,28 calix[4]arenes,29 and neutral nitrogen donors 5, 7, 15–27. For example, Luo et al 3 have studied the synergistic extraction of cerium from sulfuric acid using mixtures of di‐(2‐ethylhexyl) phosphoric (D2EHPA) and 2‐ethylhexylphosphonic acid mono‐2‐ethylhexyl ester (HEHEHP) and have determined the synergistic enhancement coefficients, the nature of the extracted complex, and the equilibrium constants.…”
Section: Introductionmentioning
confidence: 99%